3PC-024 The effects of freeze–thaw cycling on the stability of the adalimumab biosimilar SB5. (24th March 2020) - Ebbers, H; Kim, J; Yun, J; Park, D; Hwang, SJ; Park, SJ
Abstract : Background and importance: Temperature excursions may occur during manufacturing, storage, the distribution process and during clinical trials. Limited data are available to hospital pharmacists to support decision making following temperature excursions. Aim and objectives: To evaluate the stability of SB5 prefilled syringes (PFS) following short term exposure to high and low temperature conditions. Material and methods: SB5 prefilled syringes obtained from a single lot were exposed to three freeze–thaw cycles in their immediate packaging. Each cycle exposed the product to low temperatures (−5±3°C, 48 hours) followed by high temperatures (30±2°C with 65±5% relative humidity (RH), 48 hours). Samples were analysed using a variety of validated methods for appearance, pH, protein concentration, container closure integrity, impurities, charge variants, oxidation, endotoxin, particulates and biological activity. Results: A total of 132 syringes underwent three freeze–thaw cycles, exposing each syringe for a total of 144 hours to 30°C and 144 hours to −5°C. Following exposure, 66 syringes were used for the analysis and 66 were retained. The effects of this thermal cycling on the critical quality attributes of SB5 from baseline is shown in table 1 . Conclusion and relevance: SB5 was stable in the immediate pack when exposed to multiple freeze–thaw cycles. These results may help hospital pharmacists assess the impact of temperature excursions during shipment or storage on product quality of SB5. References and/or acknowledgements: Conflict of interest: Corporate sponsored research or other substantive relationships: HE is an employee of, and holds stock in Biogen, responsible for the commercialisation of SB5. JK, JY, DP, SJH and SJP are employees of Samsung Bioepis, the marketing authorisation holder of SB5.